Estimation of relative load from bar velocity in the full back squat exercise - Sanchez-Medina, L.; Pallares, J. G.; Perez, C. E.; Moran-Navarro, R.; Gonzalez-Badillo, J. G (Sports Medicine International Open, 2017)
The use of bar velocity to estimate relative load in the back squat exercise was examined. 80 strength-trained men performed a progressive loading test to determine their one-repetition maximum (1RM) and load-velocity relationship. Mean (MV), mean propulsive (MPV) and peak (PV) velocity measures of the concentric phase were analyzed. Both MV and MPV showed a very close relationship to %1RM (R2=0.96), whereas a weaker association (R2=0.79) and larger SEE (0.14 vs. 0.06?m·s-1) were found for PV. Prediction equations to estimate load from velocity were obtained. When dividing the sample into 3 groups of different relative strength (1RM/body mass), no differences were found between groups for the MPV attained against each %1RM. MV attained with the 1RM was 0.32±0.03?m·s-1. The propulsive phase accounted for ~82% of concentric duration at 40% 1RM, and progressively increased until reaching 100% at 1RM. Provided that repetitions are performed at maximal intended velocity, a good estimation of load (%1RM) can be obtained from mean velocity as soon as the first repetition is completed. This finding provides an alternative to the often demanding, time-consuming and interfering 1RM or nRM tests and allows implementing a velocity-based resistance training approach.